2003
DOI: 10.1021/es020899f
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Very Tight Sequestration of BTEX Compounds in Manufactured Gas Plant Soils Based on Selective Supercritical Fluid Extraction and Soil/Water Partitioning

Abstract: Benzene, toluene, ethylbenzene, o-, m-, and p-xylenes (BTEX), and polycyclic aromatic hydrocarbons (PAHs) were extracted from eight manufactured gas plant (MGP) soils from sites that had been abandoned for several decades. Supercritical fluid extraction (SFE) with pure carbon dioxide demonstrated the presence of BTEX compounds that were highly sequestered in both coal gas and oil gas MGP soils and soots. Benzene was generally the slowest compound to extract from all samples and was even more difficult to extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Poling (2007). Other data are from (Hawthorne and Miller, 2003), adapted from Bartle et al (1991), Miller et al (1996), and Mackay and Shiu (1977). …”
Section: Organics Of Concern Properties and Selection Of Key Compoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Poling (2007). Other data are from (Hawthorne and Miller, 2003), adapted from Bartle et al (1991), Miller et al (1996), and Mackay and Shiu (1977). …”
Section: Organics Of Concern Properties and Selection Of Key Compoundmentioning
confidence: 99%
“…Francis (1954) reported that benzene and near-critical CO 2 are fully miscible at room temperature and 6.6 MPa. Hawthorne and Miller (2003), in a study related to supercritical fluid extraction of benzene from soils, indicate that benzene and SCC are fully miscible.…”
Section: A4 Binary Benzene + Co 2 Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme hydrophobicity of POPs, many of which have K ow values near or above 10 6 , purportedly resulted in their preferential adsorption to soil organic matter. Sequestration or irreversible adsorption of POPs in the soil matrix over time (Hawthorne and Miller 2003) was also assumed to reduce their bioavailability to soil microbes, fauna such as earthworms (Morrison et al 2000) and, by extension, to flora. Consequently, half-lives of the chemicals in soils range from years (Handbook of Environmental Degradation Rate 1991), to decades (Mattina et al 1999) and even centuries (Kurt-Karakus et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study, Hawthorne and Miller (2003) used increasingly vigorous supercritical fluid extraction (SFE) conditions to characterize the degree of sequestration for benzene, toluene, ethylbenzene, o-, m-, p-xylenes in addition to the PAHs from 8 of the samples investigated in the previous study. For all the samples, the largest slowly desorbed fractions of total chemical present requiring the strongest SFE conditions were found to be benzeneNm,pxyleneNnaphthalene.…”
Section: Relevance To Other Vocsmentioning
confidence: 99%